Pengelolaan Permukiman Pesisir dan di Atas Air Berkelanjutan di Desa Teluk Sunting, Kabupaten Kepulauan Anambas Provinsi Kepulauan Riau - Harmini, Harmini; Wihadanto, Ake; Soesanta, Prabawa Eka (Jurnal Teknologi Lingkungan Lahan Basah, 2024)
Coastal settlements are highly vulnerable because they are greatly affected by global climate change. Population growth will further increase the use of unorganized built space in the coastal area of Teluk Sunting Village which in the future could lead to conflict as a result of regulations and policies regarding coastal areas. This research was conducted in the coastal residential area of Teluk Sunting Village, Central Siantan District, Anambas Islands Regency. The research method consists of data collection techniques, sampling techniques, data requirements, data presentation, analysis methods and data analysis techniques. The results obtained are that the administrative area of Teluk Sunting Village contains cultivation and protected areas according to the RTRW Spatial Pattern Plan. The area is 5.29 Ha of mangrove ecosystem area and 34.83 Ha of protected forest area. Area of 19.22 Ha cultivation area. The environmental quality results obtained in RT 1 settlements are low quality settlements, RT 3 is medium quality settlements and RT 2 and RT 4 settlements are high quality settlements. The conclusions obtained from the four approaches taken to identify land use patterns, namely land use patterns, land use and use with land tenure, conformity with the RTRW and conformity with the zoning of Aquatic Tourism Parks, are in accordance with the designation. The involvement of stakeholders in the management of coastal and water areas in Teluk Sunting Village is very appropriate to support and ensure the sustainability of the area in the future.